Standard Operating Procedure (SOP) for leaf sample collection for genotyping - Olutegbe, A.; Nnadi, A.; Ige, A.; Nafiu, K.; Ogungbesan, B.; Kayondo, S.I.; Mbanjo-Edwige, G.; Rabbi, I. (International Institute of Tropical Agriculture, 2024)
Application of deoxyribonucleic acid (DNA) technology in plant breeding offers an opportunity to enhance and accelerate genetic gain. Molecular markers, which are DNA or gene sequences with known locations on chromosomes are used as a tool for identification and genetic analysis. DNA extraction is the starting point and a critical step for genetic analysis. DNA can be extracted from diverse sources, including seeds and leaves of plants. Proper plant collection and storage conditions are essential for successfully extracting DNA of high quality and quantity from plants.